1988
DOI: 10.1039/c39880000602
|View full text |Cite
|
Sign up to set email alerts
|

Reversible homogeneous catalysis of carbon dioxide hydrogenation/reduction at room temperature and low pressures

Abstract: The reaction between Con, H2, and Me2NH to yield HC(0)NMe2 and H20 is catalysed by [Pt2(pdppm)3] (dppm = Ph2PCHZPPh2) under unprecedented mild conditions in toluene solution, and the catalysis is readily reversible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“… 4 In 1998, Vaska and coworkers developed the first Pt-catalyzed formylation of amine with CO 2 and H 2 . 5 This study has encouraged further developments using other transition metal catalysts 6 or metal-free catalysts. 7 In 2012, Cantat and coworkers achieved the first organocatalytic formylation of amines with CO 2 and hydrosilane, catalyzed by triazabicyclodecene (TBD).…”
Section: Introductionmentioning
confidence: 92%
“… 4 In 1998, Vaska and coworkers developed the first Pt-catalyzed formylation of amine with CO 2 and H 2 . 5 This study has encouraged further developments using other transition metal catalysts 6 or metal-free catalysts. 7 In 2012, Cantat and coworkers achieved the first organocatalytic formylation of amines with CO 2 and hydrosilane, catalyzed by triazabicyclodecene (TBD).…”
Section: Introductionmentioning
confidence: 92%
“…Examples of metal-catalyzed N-H formylation with CO2 are shown in Table 3, and the structures of selected catalysts are shown in Scheme 20. The formylation of an N-H bond of primary or secondary amines to yield formamide derivatives was reported using precious-metal (Ir, Pd, Pt, and Ru) [164,[171][172][173][174][175][176] catalysts, e.g., (PPh3)3Ir(CO)Cl [167], PdCl2 [172], [Pt2(μ-dppm)3] (dppm = bis(diphenylphosphino)methane) [173,177], RuCl2(PMe3)4 [178] RuCl2(dppe) (dppe = bis(diphenylphosphino)ethane) [164,179], and Ru(PNP)(CO)(H)Cl (PNP = N,N-bis(2-(diphenylphosphinoethyl)methylamine) (Scheme 20), and H2 as the reductant at a usually moderate to high turnover number (TON). Similar N-H formylation was also explored using non-preciousmetal catalysts, particularly with phosphine ligands, e.g., MX2/dmpe (M = Co, Cu, Fe, Ni, and Mn; X= Cl − , CH3CO2 −, and acac − ; dmpe = bis(dimethylphosphino)ethane) [180], Cu(PPh3)3Cl [141,150], M(BF4)2/PP3 (M = Fe and Co; PP3 = tris[2-(diphenylphosphino)ethyl]phosphine), and Fe(BF4)2/PAr3 (PAr3 = tris(2-(diphenylphosphino)phenyl)phosphine) [19,[181][182][183].…”
Section: Diagonal (Reductive) Co 2 Functionalizationmentioning
confidence: 99%
“…The use of NH3 as a substrate presents a further challenge for N-H bonds are potentially active in the formylation with CO2 and H2. The iridium complex [IrCl(CO)(PPh3)2] was an effective catalyst for the synthesis of N-formylamine from NH3, CO2 and H2, in toluene or methanol solutions at 125 °C (Scheme 1) 28,29 . After 10 days, a TON of 1145 was obtained.…”
Section: Formamides Synthesis From Coand Amines 21 Iridium Catalyst mentioning
confidence: 99%
“…[Pt2(µ-dppm)3] (dppm: bis(diphenylphosphino)methane) was proved to be an active catalyst for the synthesis of DMF starting from DMA and carbon dioxide (1-1.2 MPa) in the presence of molecular hydrogen (6.7-9.4 MPa) at 75 °C in toluene ( Table 1, entry 4) 37 . Importantly, the authors demonstrated that DMF could be achieved under very mild reaction conditions, i.e., 0.1 MPa of each of the three gas reactants, even at room temperature.…”
Section: Platinum Catalyst Systemmentioning
confidence: 99%